Factores clave que determinan la competitividad del sector vitivinícola del Valle del Cauca en el ámbito de la exportación (2024)
Colombia and the Cauca Valley is an important wine sector of the national agroindustry, which has entered the regional culture, and where its population in its rural environment cultivates, becoming a very competitive product. The economic level that this production reaches is within the three spheres of the economic sector that are contemplated as it is: country, sector and company